1999
DOI: 10.1097/00005768-199912000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Stroking parameters in top level swimmers with a disability

Abstract: These findings, which are discussed, showed that stroke index (SI = V.SL) could be used as a sensitive criterion to assess the swimmer with a disability in relationship to his classification level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 13 publications
4
29
1
9
Order By: Relevance
“…It has been demonstrated that the dislocation velocity in swimming is the product of the stroke rate (SR) by the stroke length (SL) and variations in the swimming velocity by training and lack of training mainly occur by modifications in SR and SL (13)(14) . For this reason, these variables have been the aim of studies on elite swimming (13,15) , educational status (16) , disabled subjects (17) and for technical analysis between swimmers and triathletes (18) .…”
mentioning
confidence: 99%
“…It has been demonstrated that the dislocation velocity in swimming is the product of the stroke rate (SR) by the stroke length (SL) and variations in the swimming velocity by training and lack of training mainly occur by modifications in SR and SL (13)(14) . For this reason, these variables have been the aim of studies on elite swimming (13,15) , educational status (16) , disabled subjects (17) and for technical analysis between swimmers and triathletes (18) .…”
mentioning
confidence: 99%
“…The 100m freestyle event in swimmers with physical impairments has been studied on several occasions from the analysis of the kinematic variables and their interaction (Daly et al, 1999;Daly et al, 2003;Pelayo et al, 1999; Pérez-Tejero, Veiga, Almena, Navandar and Navarro, 2017) or its time features regarding variation and progression along different competitions (Fulton, Pyne, Hopkins, and Burkett, 2009). This is the only event in which all sport classes compete at Paralympic level, and it is the most popular (Daly et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Daly, Malone, Vanlandewijck, and Steadward, 1999;Djobova, Mavromati, and Daly, 2002;Pelayo, Sidney, Moretto, Wille, and Chollet, 1999) have shown how SL increased significantly as did the functional class. Regarding SR, no significant differences were found between sport classes and/or swimmers without impairments (Pelayo et al, 1999). At the same time, in this same study, while comparing genders, a significant difference was only found in the SL values, which were found to be higher among the males.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations